Application of FFT-analyzed umbilical artery doppler signals to fuzzy algorithm - Hardalaç, F?rat; Biri, Aydan; Sucak, Ayhan (My University, 2004)
Doppler signals, recorded from the umbilical artery of 60 women with pregnancy, were transferred to personal computer via a 16-bit sound card. The fast Fourier transform (FFT) method was applied to the recorded signal from each patient. Because FFT method inherently cannot offer a good spectral resolution at highly turbulent blood flows, it sometimes causes wrong interpretation of Doppler signals. In order to avoid this problem, umbilical artery Doppler blood flow velocity parameters were introduced to a fuzzy algorithm. It is observed that the fuzzy algorithm gives true results for interpretation of umbilical artery blood flow velocity parameters. Forty-five blood flow velocity parameters of 60 women with pregnancy and 15 parameters in training data have been used in a fuzzy system as testing data. The overall success ratio in training data and the testing data were 95.55 and 93.35% respectively.
Keywords: Doppler ultrasound; FFT method; fuzzy logic; perinatal surveillance; umbilical artery